Evaluation of chemicals and bioagents against Sclerotium rolfsii causing southern blight of bell pepper (Capsicum annuum) - DINESH SINGH, CHITRA SRIVASTAVA; MOBIN AHMAD, M. NARAYANA BHAT*, H.R. SARDANA (Indian Phytopathology, 2015)
The experiment was conducted to evaluate chemicals and bioagents against Sclerotium rolfsii causing southern blight on bell pepper (Capsicum annuum L.) during 2010-11 and 2011-12 at Karnal, Haryana. Southern blight on bell pepper is an emerging disease in Haryana. Trichoderma harzianum isolates 1 and 5 and T. viride isolates 1 and 3 inhibited mycelial growth by >60% and completely inhibited sclerotial production in vitro. Strobulirin, triazole and carboxamides had ED 50<0.5 Âµg/ml against S. rolfsii in vitro. Selected bioagents reduced disease incidence by 15.5-37.5% and increased yield by 14.8-30.3% under field conditions.